Analisis Aplikasi System Ai Robotnisasi pada Kualitas Permesinan Mesin CNC di PT Evergrown Technology Batam - Kendek, Yohanis Sampe; Palungan, Musa Bondaris; Nitha, Nitha (Politeknik Negeri Padang, 2025)
This study aims to analyze the application of Artificial Intelligence (AI) and robotization systems on the machining quality of CNC machines at PT Evergrown Technology Batam. The research focuses on two primary indicators of machining quality: surface roughness and product cylindricity, which were experimentally measured in a controlled laboratory environment. Additionally, production process efficiency was examined through indicators such as production time, production costs, defect rates, and tool wear. Data were collected from 25 observation units selected through purposive sampling and analyzed using a quantitative approach with the assistance of SPSS version 2.3. The analytical methods employed include descriptive statistics, simple linear regression, one-way ANOVA, and comparative analysis to evaluate pre- and post-implementation conditions of AI and robotization systems. The results indicate that the implementation of AI and robotization has a significant impact on improving machining quality and production efficiency, as evidenced by a significance value of p < 0.05. These findings suggest that integrating AI and automation into production processes is a strategic move for advancing modern manufacturing industries.